Domain‐General Auditory Processing Partially Explains Second Language Speech Learning in Classroom Settings: A Review and Generalization Study. Issue 3 (22nd February 2021) - Saito, Kazuya; Suzukida, Yui; Tran, Mai; Tierney, Adam
Abstract: To date, a growing number of studies have shown that domain‐general auditory processing, which prior work has linked to L1 acquisition, could explain various dimensions of naturalistic L2 speech proficiency. The current study examined the generalizability of this topic to L2 speech learning in classroom settings. The spontaneous speech samples of 39 Vietnamese English‐as‐a‐foreign‐language learners were analyzed for fluent and accurate use of pronunciation and lexicogrammar and linked to a range of variables in their auditory processing profiles. The results identified moderate‐to‐strong correlations between the participants' accurate use of lexicogrammar and audio‐motor sequence integration scores (i.e., the ability to reproduce melodic/rhythmic information). However, the relationship between phonological proficiency and auditory acuity (i.e., the ability to encode acoustic details of sounds) was nonsignificant. Although the findings support the audition‐acquisition link to classroom L2 speech learning to some degree, they only suggest that this link is robust for the acquisition of lexicogrammar information. Abstract :